Advances in Pathogenesis of Idiopathic Membranous Nephropathy - Zhifeng Xu; Lu Chen; Huiling Xiang; Chun Zhang; Jing Xiong (Karger Publishers, 2020)
Background: Membranous nephropathy (MN), a major cause of nephrotic syndrome, has attracted people's attention in recent years for its growing prevalence. It is the second or third leading cause of ESRD in patients with primary glomerulonephritis and is the leading glomerulopathy that recurs after kidney transplantation. Summary: MN can be classified as idiopathic membranous nephropathy (IMN) and secondary MN. The discovery of the M-type phospholipase A2 receptor (PLA2R) and thrombospondin type-1 domain-containing 7A (THSD7A) provides the new diagnostic methods and treatment strategies for IMN on the molecular level. The study on single nucleotide polymorphism of IMN genes, such as the single M-type phospholipase A2 receptor 1 (PLA2R1) gene and human leukocyte antigen (HLA) gene, explains the pathogenesis of the disease from the perspective of genetics and conforms to the trend of the era of precision medicine. Key Messages: This review focuses on advances in the pathogenesis of IMN, including molecular and genetic pathogenesis, as well as discussing the diagnostic and treatment guiding value brought by these new discoveries.